Theorem Of paythagores explain
Answers
Answered by
4
The square of length of hypotenuse= The square of length of one side+ The square of length of another side
In short,
![{(ab)}^{2} = {(bc)}^{2} + {(ca)}^{2} {(ab)}^{2} = {(bc)}^{2} + {(ca)}^{2}](https://tex.z-dn.net/?f=+%7B%28ab%29%7D%5E%7B2%7D++%3D++%7B%28bc%29%7D%5E%7B2%7D++%2B++%7B%28ca%29%7D%5E%7B2%7D+)
Here ab is the length of hypotenuse. bc is the length of one side and ca is the length of another side.
HOPE IT HELPS! ^_^
In short,
Here ab is the length of hypotenuse. bc is the length of one side and ca is the length of another side.
HOPE IT HELPS! ^_^
Answered by
5
your question = Explain Pythagoras theorem
Answer = refer to the above attachment
BE BRAINLY
Answer = refer to the above attachment
BE BRAINLY
Attachments:
![](https://hi-static.z-dn.net/files/d1b/8181e7d373159b2dc1609206b2a900c6.jpg)
Similar questions